Children born of a gift: will the widespread availability of genetic testing end anonymity? - Marinelli, Susanna; Petousis, Stamatios; Margioula-Siarkou, Chrysoula; Lopez, Alessandra; Billone, Valentina; Montanari Vergallo, Gianluca (Acta Biomedica Atenei Parmensis, 2024)
In the field of genetics, the proliferation of direct-to-consumer genetic testing tools is calling into question the principle of gamete donor anonymity, still codified in many legislative frameworks. While ethicists debate whose rights should be prioritized, many donor-conceived people and intended parents are currently sharing their genetic information. Those who attempt to conceive with donor sperm or eggs face many obstacles: they often experience the social stigma associated with infertility, and therefore choose not to reveal the existence of a donor to their children. Sometimes it is the children, when they are informed that they were conceived through gamete donation, who claim the right to know their genetic origins. Many states still do not allow this possibility because the principle of anonymity is in force. In this scenario, it is necessary to discuss the right to know one’s genetic origins and the need for legislation on heterologous fertilization, since the lack of specific legislation makes discrimination and inequality more likely, for homosexual as well as heterosexual intended parents. This article focuses on the importance of accessing information in relation to identity formation, laying out the complexities and distinctive features that such dynamics entail.